Literature Review on Some Relevant Variables in Goal Setting in Sport. - Díaz-Ocejo, Jaime; Mora-Mérida, Juan Antonio (Anales de Psicología / Annals of Psychology, 2013)
The purpose of this paper is to examine the influence of some relevant variables in the goal setting process, such as the proximity, specificity, difficulty and effectiveness, throughout the literature review. Accordingly, we follow the guidelines outlined by relevant authors in this topic. Results are not conclusive with regards to the proximity, specificity and difficulty in goal setting. Contrarily, it is found a more consistent evidence in favor of the effectiveness in the use of this psychological strategy as a tool to enhance motor skills performance.